2006
DOI: 10.1111/j.1471-4159.2006.04131.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive loss of a glial potassium channel (KCNJ10) in the spinal cord of the SOD1 (G93A) transgenic mouse model of amyotrophic lateral sclerosis

Abstract: Transgenic mice expressing the superoxide dismutase G93A mutation (SOD1 G93A ) were used to investigate the role of glial inwardly rectifying K + (Kir)4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 56 publications
14
74
0
3
Order By: Relevance
“…(Vizuete et al, 1999;Tomà s-Camardiel et al, 2005). This concept was already approached by Kaiser et al who observed a progressive loss of Kir4.1 channels and a slight increase in AQP4 protein in the mouse ALS model (Kaiser et al, 2006). Our work using the rat ALS model not only confirms the increase in AQP4 observed in the mouse model but decipher the localization where AQP4 expression is increased.…”
Section: Discussionsupporting
confidence: 84%
“…(Vizuete et al, 1999;Tomà s-Camardiel et al, 2005). This concept was already approached by Kaiser et al who observed a progressive loss of Kir4.1 channels and a slight increase in AQP4 protein in the mouse ALS model (Kaiser et al, 2006). Our work using the rat ALS model not only confirms the increase in AQP4 observed in the mouse model but decipher the localization where AQP4 expression is increased.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, we find an increased expression of AQP4 in perivascular as well as perineural membranes, in addition to the neuropil, accompanied by elevated expression of GFAP, following neurotoxic treatment. This pattern is in line with several disease models, including ischemic stroke (449) (348,365) and spongiform encephalopathy (349). As these chronic neurodegenerative diseases share similarities with PD, they provide an indication of AQP4 expression in relation to regional, progressive cell death.…”
Section: Selective Vulnerability Mediated By the Glial Microenvironmesupporting
confidence: 81%
“…Potentially, a PD model including LBs would have painted a different picture on AQP4 distribution in PD than our models, as astrocytes are known to accumulate α-synuclein (452). Further, in models of ALS, a slight upregulation of perivascular AQP4 and GFAP has been described in mice (365), whereas vast upregulation of AQP4 mRNA and protein has been shown in rats, where expression was increased around vessels together with GFAP, and in motoneuron perikaya (348). These results also indicate that differences between species may be present, which has also been found between bovine and mice in spongiform encephalopathy, with more pronounced expression and earlier upregulation of AQP4 in bovine (349).…”
Section: Selective Vulnerability Mediated By the Glial Microenvironmementioning
confidence: 93%
“…After this, denervation of the motor units and loss of maximal force begins (Kennel et al, 1996, Frey et al, 2000, Fischer et al, 2004, Hegedus et al, 2007, Hegedus et al, 2008, but the impairment of normal function in the mouse is subtle and onset of overt symptoms is several weeks off, even in the most severe models. Just before the impending functional loss, several of the last changes before overt onset of symptoms involve the glia: activation of astrocytes, expression of different splice variants of EAAT2, decreased expression of the GluR2 subunit, and decreased number of glial K + channels (Bruijn et al, 1997, Bendotti et al, 2001, Sasaki et al, 2001, Munch et al, 2002, Warita et al, 2002, Fischer et al, 2004, Ignacio et al, 2005, Kaiser et al, 2006. It is tempting to assume that the order of appearance of the altered parameters represents a chain reaction of events, but this is not necessarily the case.…”
Section: Timeline Of Deficitsmentioning
confidence: 99%
“…The glial response is thought to influence the progression, but not the onset, of the disease (Beers et al, 2006, Boillee et al, 2006, Philips and Robberecht, 2011. Presymptomatic involvement of the glia includes a reduction of glial K + channel expression shortly before the onset of symptoms (Kaiser et al, 2006) and later in the course of the disease, a reduced expression of astroglial glutamate transporters, GLT1/EAAT2 which mediate glutamate reuptake at synapses and help prevent glutamate excitotoxicity (Bruijn et al, 1997, Bendotti et al, 2001, Warita et al, 2002. Earlier alterations in EAAT2 function are likely due to expression of different splice variants rather than decreased expressions levels (Sasaki et al, 2001, Munch et al, 2002, Ignacio et al, 2005.…”
Section: Non-cell Autonomous Deficits: Astrocytes and Glutamate Excitmentioning
confidence: 99%